Pertanggung Jawaban Pidana Pelaku Penipuan Tautan Undangan Melalui Whatsapp Ditinjau dari Undang-Undang Nomor 19 Tahun 2016 Tentang Informasi Transaksi Elektronik - Yaqin, Moh. Ainul; R. Hariandja, Tioma; Winiari wahyuningtyas, Yuli; Hoiru Nail, Muhammad (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2024)
The rapid advancement of technology has brought many benefits to society, making it easier and helping to meet their needs through various technologies. However, along with this development, problems such as fraud through WhatsApp applications have also emerged. One of the modus operandi is the fraud of courier receipts or from the sender's expedition party. Therefore, the formulation of the research problem is whether perpetrators of fraud through WhatsApp invitation links can be subject to criminal sanctions, and what legal efforts can be made by victims of fraud through WhatsApp invitation links. The purpose of this study is to determine whether fraud through WhatsApp invitation links can be subject to criminal sanctions, and to determine what legal efforts can be made by victims of such fraud. The research method used is the typology of normative legal research, which is research conducted on written regulations, as well as library research or documentary studies, because this research mostly uses secondary data such as books and official documents. The approach used in this research is the statutory approach, case approach, and conceptual approach. In addition, this study also uses primary and secondary legal material sources. The first discussion result shows that fraud through WhatsApp invitation links can be subject to criminal sanctions based on Article 378 of the Criminal Code and Article 28 paragraph (1) of the ITE Law. Victims can take legal action by reporting such criminal acts to the Police in accordance with Article 4 paragraph (1) of Law Number 23 of 2007 concerning the Legal Jurisdiction of the Indonesian National Police. Victims can also resolve their issues through litigation or non-litigation.